Human journeys in the digital age: Advances and challenges in Digital Historical Migration Studies - Arthur, Paul Longley; Smith, Isabel (Frontiers in Human Dynamics, 2022)
Accelerations in migration, mobility, and processes of globalization in recent decades have intersected with parallel developments in information and communications technology (ICT). These advances have had profound influences on historical and cultural research. With reference to a diverse range of international projects, this paper outlines major directions and opportunities in the growing field of Digital Historical Migration Studies (DHMS). The “digital turn” brings opportunities for integrating data on macro and micro scales, and finding new ways to combine and explore tensions between quantitative and qualitative materials, and between external observations of migrants and migration and self-representations by migrants. The plural and fluid nature of digital content also lends itself to multifaceted representations of migration that illustrate the complexities of lived experiences, and individual and collective identities. At the same time, digitalization in historical migration studies underscores the tensions between technological advances and methodological shifts, the need for self-reflexive approaches, the politics and power structures underlying migration data, and the ethical concerns around protecting migrants' data, privacy, and agency.